Exploration of the low arithmetic achievement on primary students: Teacher’s perspectives - Embong, Zulmaryan; Khalid, Madihah; Mohamed Adnan, Nor Syamimi; Razikin, Mohyani (IOP Publishing, 2020)
According to the Trends in International Mathematics and Science Study (TIMSS), the level of Mathematics achievement in Malaysia for primary levels has seemed to be steadily decreased from 2003 to 2007. Although there are many efforts done by the government, NGOs, societies and parents in order to increase students’ performance in mathematics, it is still decreasing significantly and unfortunately the same problems carry until when it comes to secondary level. Therefore, the purpose of this study was to identify the causes of weaknesses of students’ achievement from the teachers’ perspectives. In addition, this paper aims to determine the effective strategies approaches for low achievement in mathematics and lastly to improvise the teaching and learning process for the future. An exclusive interview with the experienced mathematics teachers from a public and private school was conducted.